2023
DOI: 10.1109/twc.2022.3220752
|View full text |Cite
|
Sign up to set email alerts
|

Composite Multiple-Mode Orthogonal Frequency Division Multiplexing With Index Modulation

Abstract: In this paper, we propose a composite multiplemode orthogonal frequency division multiplexing with index modulation (C-MM-OFDM-IM) scheme to increase the spectral efficiency (SE) of OFDM-IM systems by extending the indexing to the energy and constellation domains. In C-MM-OFDM-IM, the information bits are mapped to not only the subcarrier activation patterns (SAPs) and modulation symbols, but also the energy allocation patterns (EAPs) and constellation activation patterns (CAPs). To cope with the practical sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 45 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…If W 0 i is the same as the composite pseudo-code W, the despread data b 0 i are calculated by Equation (17) and are equivalent to the real index data d 0 i .…”
Section: Index Data Bitsmentioning
confidence: 99%
See 1 more Smart Citation
“…If W 0 i is the same as the composite pseudo-code W, the despread data b 0 i are calculated by Equation (17) and are equivalent to the real index data d 0 i .…”
Section: Index Data Bitsmentioning
confidence: 99%
“…The proposed scheme uses the corresponding activation pseudo-code to modulate and decode data according to the pseudo-code activation principle and the correlation peak judgement mechanism and converts the antenna index in SM into the index of the spreading code. So far, many studies [15][16][17] have shown that the OFDM-IM technique and its improved technique have a better bit error rate (BER) performance than traditional OFDM under the same spectral efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this objective, superposition coding (SC) is performed at the transmitter and successive interference cancellation (SIC) at the receiver [ 13 ]. Moreover, combining NOMA with high spectral efficient multiple-input multiple-output (MIMO) techniques, such as quadrature spatial modulation (QSM) [ 14 , 15 ], can further enhance the spectral efficiency and increase the capacity of non-terrestrial wireless networks [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter wave (mmWave) communication is a promising technology that plays a major role in fifth-generation (5G) wireless communications owing to its wide bandwidth [ 1 ], sufficient spectral-efficiency [ 2 , 3 , 4 , 5 ] and high quality of service (QoS) [ 6 , 7 , 8 , 9 , 10 ]. In highly directive wireless communications, beamforming is a signal processing tool used to steer, shape, and control multiple antenna directions efficiently, which minimizes transmission losses [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%